Non-invasive preimplantation genetic screening using array comparative genomic hybridization on spent culture media: a proof-of-concept pilot study. Issue 6 (June 2017) - Feichtinger, Michael; Vaccari, Enrico; Carli, Luca; Wallner, Elisabeth; Mädel, Ulrike; Figl, Katharina; Palini, Simone; Feichtinger, Wilfried
Abstract: The aim of this pilot study was to assess if array comparative genomic hybridization (aCGH), non-invasive preimplantation genetic screening (PGS) on blastocyst culture media is feasible. Therefore, aCGH analysis was carried out on 22 spent blastocyst culture media samples after polar body PGS because of advanced maternal age. All oocytes were fertilized by intracytoplasmic sperm injection and all embryos underwent assisted hatching. Concordance of polar body analysis and culture media genetic results was assessed. Thirteen out of 18 samples (72.2%) revealed general concordance of ploidy status (euploid or aneuploid). At least one chromosomal aberration was found concordant in 10 out of 15 embryos found to be aneuploid by both polar body and culture media analysis. Overall, 17 out of 35 (48.6%) single chromosomal aneuploidies were concordant between the culture media and polar body analysis. By analysing negative controls (oocytes with fertilization failure), notable maternal contamination was observed. Therefore, non-invasive PGS could serve as a second matrix after polar body or cleavage stage PGS; however, in euploid results, maternal contamination needs to be considered and results interpreted with caution.